Osseous metaplasia and mature bone formation with extramedullary hematopoiesis in follicular adenoma of thyroid gland - Harsh Mohan; Dimri Parul; Nagarkar Nitin (Wolters Kluwer Medknow Publications, 2009)
Follicular adenomas of the thyroid may be subjected to degenerative changes like hemorrhagic and cystic changes, fibrosis, and calcification. Mature bone formation is a rare phenomenon, but extramedullary hematopoiesis (EMH) has also been rarely reported in thyroid gland. The combination of mature bone formation and EMH is rarer and has been reported, in a single case report, in a multinodular goitre. We describe a case of follicular adenoma with histologically proven osseous metaplasia and mature bone formation with EMH in a middle- aged woman, which, to our knowledge, is the first case in English language literature.